Ontogenesi del significato, natura umana e realtà: per una teoria sociocostruttivista dello sviluppo linguistico e cognitivo - Gargani, David (Rivista Italiana di Filosofia del Linguaggio, 2012)
The issue of ontogeny of meaning is closely connected to philosophical questions concerning both the relationship between language, thought and reality and the problem of human nature. Realist philosophers maintain that the world is intrinsically organized according to genres and species, with human knowledge reflecting this organization in terms of how our most basic concepts are developed and employed. From this point of view the ontogeny of meaning would consist of a simple naming of concepts, those which are already at hand. To examine these questions and the issues circulating around it, we turn away from realist approaches by adopting a pluralistic and socio-constructivist perspective that allows for the fact that physical reality is mutable, highly complex and may be interpreted in many different ways. The flexibility and creativity of the human mind, and of language, enables different cultures to investigate the world in different ways, giving rise to different concepts concerning the way reality functions. Children, in particular, construct a plurality of concepts through a selection of relevant traits related to how successful their actions in the physical world are, as well as through their communicative praxis in the social world. These two processes combine to become one in the ontogeny of meaning: children become able to select the semantic properties that identify the meanings of their own languages. It follows that experiential concepts and knowledge are reorganized in a web of sign relations. Hence the capacity for meta-representation can develop in such a way that children become able to reflect on their own thoughts. At the end they will construct an articulate and explicit web of semiotically organized concepts